Development of an acute, short-term exposure model for phosgene. (13th October 2019) - Hobson, Stephen T.; Casillas, Robert P.; Richieri, Richard A.; Nishimura, Robert N.; Weisbart, Richard H.; Tuttle, Rick; Reynolds, Glenn T.; Parseghian, Missag H.
Abstract: Phosgene is classified as a chemical warfare agent, yet data on its short-duration high concentration toxicity in a nose-only exposure rat model is sparse and inconsistent. Hence, an exposure system for short-term/high concentration exposure was developed and characterized. Herein, we report the median lethal concentration (LC50 ) for a 10-min nasal exposure of phosgene in a 24-h rat survival model. Male Wistar rats (Envigo) weighing 180–210 g on the day of exposure, were exposed to phosgene gas via nose-only inhalation using a system specifically designed to allow the simultaneous exposure and quantification of phosgene. After 24 h, the surviving rats were euthanized, the lung/body mass ratio determined, and lung tissues analyzed for histopathology. Increased terminal airway edema in the lungs located primarily at the alveoli (resulting in an increased lung/body mass ratio) coincided with the observed mortality. An LC50 value of 129.2 mg/m 3 for a 10-min exposure was determined. Furthermore, in agreement with other highly toxic compounds, this study reveals a LC50 concentration value supportive of a nonlinear toxic load model, where the toxic load exponent is >1 ( n e = 1.17). Thus, in line with other chemical warfare agents, phosgene toxicity is predicted to be more severe with short-duration, high-concentration exposures than long-duration, low-concentration exposures. This model is anticipated to be refined and developed to screen novel therapeutics against relevant short-term high concentration phosgene exposures expected from a terrorist attack, battlefield deployment, or industrial accident.